Eine Slawische une Baltische Erdgottheit Slovanska in baltska boginja zemlje - Eckert, Rainer (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">On the basis of tradition and extent sources the author reconstructs the characteristics and the development of an East Slavic and Baltic earth deity.